ERUPTIVE VELLUS HAIR CYSTS - Tavares-Bello, Rui; Tellechea, Óscar (Journal of the Portuguese Society of Dermatology and Venereology, 2014)
The case of a 6 year old Caucasian male bearing, for the last 12 months, asymptomatic nondescript, flesh colored papules on his anterior thorax and arms is reported. Upon pathological examination, the diagnosis of Eruptive Vellus Hair Cysts was confirmed. A brief revision of this entity, as well as its nosographic framing within the cyst-like developmental skin abnormalities is done.